Employee Dismissal in the Pandemic Era: A Review of the Effects of Changes in the Work Environment and Layoff Policy by Companies - Muhamad Ammar Muhtadi (West Science Social and Humanities Studies, 2023)
Employee dismissals have become an increasingly complex issue in the era of the COVID-19 pandemic. This study aims to explore the effect of changes in the work environment and layoff policies by companies on employee dismissals during the pandemic. This study used a qualitative approach with in-depth interviews as a data collection technique. The results showed that changes in the work environment and layoff policies by companies had a significant impact on the decision to dismiss employees. Companies tend to choose to lay off employees who are considered less productive and difficult to adapt to changes in the work environment. However, the layoff policy taken by the company also has the potential to cause problems related to employee rights and can worsen the economic situation of people affected by the pandemic. Therefore, strong legal protection is needed for employees and coordination between companies, governments, and related institutions in taking layoff policies during the pandemic.